SISTEM INFORMASI MANAJEMEN SURAT PADA SMK TARUNA BALEN BOJONEGORO DENGAN MENGGUNAKAN PHP DAN MYSQL - Dahlan Susilo; Firdhaus Hari Syahputra; Sri Huning Anwariningsih (Fakultas Sains, Teknologi dan Kesehatan Universitas Sahid Surakarta, 2019)
The development of information system technology makes everyone need presentation of information quickly and efficiently. The Taruna Vocational High School (SMK) under the foundation of Tholobin Roudlotut / Ma'arif NU Institution are still manually processing correspondence data both in letter filing and mailing. This can makes frequent errors in mail data storing and searching. In solving the problem, a latter data processing system is needed to support the success in data collection and storage of correspondence. System Information processing correspondence is discussed about processing and archiving mail. The objective of this system is to build a web-based mail management information system at Taruna Balen Vocational High School, Bojonegoro. Data collection method used interview method, observation and literature review. The method used Waterfall Method. The programming language was PHP and HTML and database used MySQL. Furthermore, tools and editors used XAMPP 3.6, Windows 10 Pro, Firefox, Adobe Photoshop CS3 and Ms. Office Visio 2010. Whereas, system testing used Alpha Testing with the Black Box method. The results of all tests on the login menu, the mail data and report menu have been successful. All systems have run quite well, safe in feasibility, easily understood in the appearance and the results obtained are appropriate to expectation. Thus, it can be concluded that the information system processing of correspondence are appropriate to expectation in processing letters data. It can be seen from the processing of letter data in inputting correspondence, the letter searching process, and also can speed up the performance of the administration staff.